Penentuan Kelas Menggunakan Algoritma K Medoids Untuk Clustering Siswa Tunagrahita - Husin Sariangsah; Wanayumini Wanayumini; Rika Rosnelly (STMIK Budi Darma, 2021)
So far, the class placement of mentally retarded students is based on the age of entering the child when registering at SLB C Muzdalifah, the Intelligence Quotient (IQ) test has not been tried for mentally retarded students in classifying student classes. It is important to group mentally retarded children to make it easier for teachers to prepare programs and implement educational services. It is important for the school to understand that in mentally retarded children there are individual differences with very large variations. That is, being at almost the same age level (calendar age and mental age) and the same education level, in fact individual abilities differ from one another. Thus, of course, special strategies and programs are needed that are adapted to individual differences. This research was made to classify and analyze data mining for class clustering students with the K-Medoids algorithm to help group students who want to occupy classes according to their level of intellectual disability. From the grouping results obtained 3 clusters, which have the highest number of students is the moderate mental retardation class and the lowest cluster is mild mental retardation, the Muzdalifah special school can prepare classes based on grouping for teaching and learning activities.